Pharmacoeconomic analysis of trastuzumab emtanzine comparing to lapatinib + capecitabine in pa-tients with HER2+ breast cancer and central nervous system metastases - A. S. Kolbin; A. A. Kurylev; Yu. E. Balykina; M. A. Proskurin; D. R. Naskhletashvili (Izdatelstvo OKI, 2018)
Aim. To perform health-economic evaluation of trastuzumab emtansine (T-DM1) in patients with HER2+ breast cancer and CNS metastases. Materials and methods. Cost-effectiveness analysis along with sensitivity analysis and budget impact analysis were performed. Direct medical costs and indirect costs (GDP loss) were accounted. Results. At 3 years modeling horizon total cost of trastuzumab emtanzine were higher comparing to lapatinib+capecitabine due to significantly higher overall survival (OS) observed in trastuzumab emtanzine group. CER OS for T-DM1 and lapatinib+capecitabine were 1 686 222 RUR/patient/ year and 1 704 486 RUR/patient/year, consequently. T-DM1 ICER (OS) was lower than cost-effectiveness threshold in Russia in 2016. Conclusions. The study showed T-DM1 is a cost-effective strategy in patient with HER2+ metastatic BC and CNS metastases.